Tailored antiplatelet agent medication in clopidogrel hyporesponsive patients before stent-assisted coiling: single-center experience - Kurniawan, Ricky Gusanto; Song, Yunsun; Kwon, Boseong; Ahn, Yura; Suh, Dae Chul (Neuroradiology, 2020)
Purpose In patients requiring stent procedures, resistance or hyperresponsiveness to antiplatelet medications is often observed. This study aims to evaluate the efficacy and safety of tailoring medications in these patients. Methods This retrospective study included 223 patients who underwent endovascular treatment for intracranial aneurysm between October 2018 and October 2019. Patients were categorized as hyporesponsive, hyperresponsive, and normoresponsive groups according to the initial PRU response. For the hypo- or hyperresponders, we tailored medication by modifying the dose or changing the drug. PRUs before and after tailoring were compared in each group. PRU reponses in patients who underwent Cytochrome P450 2C19 (CYP2C19) genotyping were also determined. Results Of the 73 clopidogrel-resistant patients, the mean PRU values after tailoring showed a greater decrease in the group that switched to prasugrel ( n = 56), from 223 to 131, than in the clopidogrel reloading group ( n = 17), from 238 to 209. In 31 hyperresponders, PRU increased from 49 to 94 after the dose adjustment. CYP2C19 genotyping showed that PRU tended to increase as the number of mutated alleles increased. There were five (2.3%) ischemic events (three transient ischemic attacks and two minor strokes) in a mean follow-up of 8 months, but no hemorrhage. Conclusions The stent-assisted coiling was successfully performed with acceptable range of ischemic events and without hemorrhage in all patients, including those who applied tailored medication. Low-dose prasugrel was effective for obtaining appropriate PRU values for initial medication as well as for clopidogrel-resistant patients. The genetic test did not provide reliable results in determining clopidogrel resistance.